Spacial Energy Distribution Manipulation with Multi-focus Huygens Metamirror - Zhuochao Wang (Nature Portfolio, 2017)
Abstract Huygens metasurface is a planar array of crossed electric and magnetic dipoles, which provide specific surface current to tailor the electromagnetic field distribution. By changing the geometrical parameters of the proposed unit cell, the manipulation range of reflection phase can achieve 2π, while the amplitude of the reflection coefficient can keep above 0.993. Based on the designed Huygens meta-atoms, a novel multi-focus Huygens metamirror is proposed at microwave range in this paper. Utilizing the meta-atoms with the desired reflection phase distribution as calculated, the incident plane wave can be converged to designated points in any desired fashion including focal number, location and intensity distribution, which exhibits outstanding manipulation capability. Our research on Huygens metamirror provides a fascinating design of multi-focus imaging in microwave region, which makes it potential applications in antenna and imaging systems.